Pancreatic Disorders (Homoeopathy for All, 2024)
Pancreas is a gland that makes  digestive enzymes and hormones  like insulin that controls blood  sugar. The enzymes are secreted into  the intestine to help digest food. It  is roughly six inches long, nestled  deep in the abdomen, between the  stomach and spine. The pancreas is  composed of two cell types, namely  exocrine and endocrine cells. The  former helps break down food, while  the latter makes insulin hormone.
Keywords: Pancreatic; Disorders